1994
DOI: 10.1152/jappl.1994.76.6.2561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of muscle length and force on endurance and pressor responses to isometric exercise

Abstract: Experiments were performed to determine whether endurance time, mean arterial pressure, or heart rate was related to either muscle length or external torque production in humans during isometric knee extension. Eight men and nine women performed isometric knee extension to the endurance limit at each of three muscle lengths, determined by knee angles of 40 degrees (0.698 rad, shortest), 60 degrees (1.047 rad, intermediate), and 90 degrees (1.571 rad, longest), and at intensities of 30 and 50% maximal voluntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
48
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 0 publications
13
48
3
Order By: Relevance
“…This knee angle dependent endurance has previously been reported; Kooistra et al [3] showed, when using a similar intermittent protocol, quadriceps times to fatigue of 87.8 and 54.9 s for 30° and 90°, respectively. The current time to fatigue differences between angles also correspond well with other studies utilising single sustained contractions to exhaustion [1,2]. The slightly longer endurance times in the present study compared to Kooistra et al [3] may be explained by methodological differences.…”
Section: Effects Of Knee Angle On Time To Fatiguesupporting
confidence: 89%
See 1 more Smart Citation
“…This knee angle dependent endurance has previously been reported; Kooistra et al [3] showed, when using a similar intermittent protocol, quadriceps times to fatigue of 87.8 and 54.9 s for 30° and 90°, respectively. The current time to fatigue differences between angles also correspond well with other studies utilising single sustained contractions to exhaustion [1,2]. The slightly longer endurance times in the present study compared to Kooistra et al [3] may be explained by methodological differences.…”
Section: Effects Of Knee Angle On Time To Fatiguesupporting
confidence: 89%
“…Unilateral studies of skeletal muscles have shown that fatigue during sustained or intermittent isometric contractions is muscle length dependent [1,2]. For example, the endurance time of submaximal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very relevant to investigate both muscle activation and muscle oxygen consumption during in vivo muscle activity at diVerent muscle lengths. Knee extensor endurance is greater at extended (short muscle length) compared to Xexed (long muscle length) knee angles during sustained isometric contractions to exhaustion, even at the same relative contraction intensity (Hisaeda et al 2001;Kooistra et al 2005;Ng et al 1994;Place et al 2005). One reason for this diVerence could be a diVerence in maximal voluntary activation between knee angles (de Ruiter et al 2004;Suter and Herzog 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It would therefore be very interesting to examine muscle activation and oxygen consumption over a range of relative contraction intensities at extended compared to Xexed knee angles. In addition, insight into potential mechanisms limiting endurance at diVerent muscle lengths found previously (Hisaeda et al 2001;Kooistra et al 2005;Ng et al 1994;Place et al 2005) may be gained by the simultaneous investigation of muscle activation and oxygen consumption.…”
Section: Introductionmentioning
confidence: 99%
“…TIME TO TASK FAILURE of a sustained submaximal isometric contraction (i.e., endurance time, ET) depends on physiological factors such as relative force level (30,35), muscle fiber type composition (16,51,77), muscular activation strategy (6,19,38), muscle size (36), and length (54,58) but also depends on psychological factors such as motivation, mood, and expectation (24). Whereas the task dependency of ET is well documented (23,25,26), little is known about muscle fatigue characteristics induced by a given task sustained until failure in different muscle groups, in the same individuals.…”
mentioning
confidence: 99%